PEMBAGIAN DAN PENANAMAN BIBIT, UPAYA REALISASI UNTUK KETAHANAN PANGAN DI DESA SIDOSARI, KECAMATAN SALAMAN OLEH MAHASISWA KKN UNTIDAR - Khoeriyah, Tifa Asifa; Meilinda, Tri Wahyuni; Mahardika, Iin Ayu; Sari, Fitri Maera; Saputri, Arka Ery; Alfian, Ficky; Mahfudz, Fairuz Binti Muhammad; Pratama, Firdhan Satria; Listyarini, Adinda Endah; Aini, Anida Nur; Sitoresmi, Mumpuni Wahyudiarti (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
The Community Service Program (KKN) of Tidar University in Sidosari Village, Salaman District, Magelang Regency, aims to support the realization of food security through the distribution and planting of seedlings and the utilization of household waste. This activity includes socialization of composting, introduction of drip irrigation systems, and assistance to the community in managing land optimally. The results of the activity show that community participation in the utilization of household waste has increased, and the effectiveness of land use can be increased. This program is expected to be sustainable to support local food security.